A hierarchical transcription factor cascade regulates enteroendocrine cell diversity and plasticity in Drosophila. - Guo, X.; Zhang, Y.; Huang, H.; Xi, R. (Nature communications, 2022)
Enteroendocrine cells (EEs) represent a heterogeneous cell population in intestine and exert endocrine functions by secreting a diverse array of neuropeptides. Although many transcription factors (TFs) required for specification of EEs have been identified in both mammals and Drosophila, it is not understood how these TFs work together to generate this considerable subtype diversity. Here we show that EE diversity in adult Drosophila is generated via an "additive hierarchical TF cascade". Specifically, a combination of a master TF, a secondary-level TF and a tertiary-level TF constitute a "TF code" for generating EE diversity. We also discover a high degree of post-specification plasticity of EEs, as changes in the code-including as few as one distinct TF-allow efficient switching of subtype identities. Our study thus reveals a hierarchically-organized TF code that underlies EE diversity and plasticity in Drosophila, which can guide investigations of EEs in mammals and inform their application in medicine.